"Effect of Communication on the Imposition of Criminal Sanctions for Homicide by Minors in Law" - Pratama, Muh Galang; Hasan, Hamza; Marilang, Marilang (Jurnal Mercusuar, 2021)
This type of research is descriptive research that analyzes qualitative data and focuses on literature review. The results show that a criminal act committed by a child is against the teachings of Islam. The causes of a child committing murder include internal factors such as family economic conditions and external factors such as environmental conditions. In Islamic law, a child will not be subject to criminal sanctions for a crime committed because they are not legally responsible until they reach adulthood. However, a judge is allowed to impose educational sanctions or payment of diyat to the victim's family or legal aid organizations. The implication of this research is that criminal acts committed by a minor should be borne by their parents or handed over to the state to provide protective measures for the child against punitive measures that would be detrimental to them. This is because minors are not legally responsible.